2022
DOI: 10.1002/jocb.560
|View full text |Cite
|
Sign up to set email alerts
|

Creativity Profiles and the Role of Interpersonal Relationships in Primary School Pupils: A Person‐Centered Approach

Abstract: This study aimed to investigate the heterogeneity of creativity and the role of interpersonal relationships for creativity subgroups among primary school students. We used latent profile analysis to identify subgroups of creativity among pupils. We then used logistic regression analysis to investigate the role of teacher-student and peer relationships in these subgroups. A total of 1,047 primary school students (M age = 10.97, SD = 0.91; 47.80% girls) completed the Chinese version of the Torrance Test of Creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 70 publications
0
1
0
Order By: Relevance
“…Four hundred forty of the remaining 451 studies did not have a unique correlation matrix of streamlined scores, or authors did not respond to our inquiries. Consequently, this phase of the extension provided 12 new correlation matrices in 11 new studies (Acar, 2023; Balci et al, 2023; Gao, 2023; Humble et al, 2018; Liu et al, 2023; Rubenstein et al, 2020, 2022; Wan, 2023; Warne et al, 2021; Yoon, 2017; Zhang et al, 2020) from the articles between 2017 and 2023. In some cases (e.g., Balci et al, 2023; Rubenstein et al, 2020, 2022), our dataset was larger than what was reported in the published work as the authors supplied raw data, some of which were not used in their publication.…”
Section: Methodsmentioning
confidence: 99%
“…Four hundred forty of the remaining 451 studies did not have a unique correlation matrix of streamlined scores, or authors did not respond to our inquiries. Consequently, this phase of the extension provided 12 new correlation matrices in 11 new studies (Acar, 2023; Balci et al, 2023; Gao, 2023; Humble et al, 2018; Liu et al, 2023; Rubenstein et al, 2020, 2022; Wan, 2023; Warne et al, 2021; Yoon, 2017; Zhang et al, 2020) from the articles between 2017 and 2023. In some cases (e.g., Balci et al, 2023; Rubenstein et al, 2020, 2022), our dataset was larger than what was reported in the published work as the authors supplied raw data, some of which were not used in their publication.…”
Section: Methodsmentioning
confidence: 99%
“…Several reviews and meta-analyses have concluded that positive interpersonal relationships enhance creativity and innovative behavior [135,136]. Individuals with strong peer relationships are more likely to acquire creative thinking and behavioral patterns through peer interactions [137]. The social cognitive model [138] suggests that students' social interactions and emotional development in the learning environment are relevant [139].…”
Section: Theoretical Implicationsmentioning
confidence: 99%